ORGANIZATIONAL CULTURE AND STRUCTURE AS DETERMINANTS OF SERVICE DELIVERY IN THE COUNTY GOVERNMENT OF KITUI - Mbiti, Japheth; Misango, Sedina (European Journal of Business and Strategic Management, 2021)
Purpose: In early years of the 21st Century, Kenya started a journey of developing a new constitution which established the devolved system of government to improve on governance gaps. Since the introduction of devolution, County governments have introduced new organizational culture and structures which assist in service delivery. Consequent to this development, the objective of the study was to determine the influence of organizational culture and structure on service delivery in the County Government of Kitui and specific objectives of the study were to establish the influence of organizational culture and organizational structure on service delivery in the County Government of Kitui. Methodology: The study adopted a descriptive research design and made use of a sample size by use of both stratified random and simple random sampling methods to establish the study sample. For effective data collection, the study was based on primary data which was both qualitative and quantitative. The data was collected through questionnaires and analyzed using Statistical Package for Social Science (SPSS) version 22.The analysis involved descriptive and inferential statistics. Data was presented in form of frequency tables for easy interpretation. Regression analysis was employed to establish the relationship between the variables. Results: The study established that organizational structure and organizational culture have significant effect on the Kitui county residence service delivery. The study concludes that the County government has implemented the constitutional structure and adopted a beneficial culture which ensures good planning procedures for effective service delivery. Unique contribution to theory, practice and policy: The study recommends that the County management should embrace good governance and promote the available cultural practices and that the structure be made shorter to empower junior officers with more authority and responsibilities.